Решить удобным способом: 4цел. 2/3 + 1цел.1/3 * 3 - 9цел.1/6

Решить удобным способом: 4цел. 2/3 + 1цел.1/3 * 3 - 9цел.1/6
Гость
Ответ(ы) на вопрос:
Гость
[latex] 4\frac{2}{3} + 3*1\frac{1}{3}- 9\frac{1}{6} = [/latex] [latex]= \frac{4*3 + 2 + 3(1*3+1)}{3}- \frac{9*6+1}{6} = [/latex] [latex]= \frac{12 + 2 + 12}{3}- \frac{55}{6} = [/latex] [latex]= \frac{26}{3}- \frac{55}{6} = [/latex] [latex]= \frac{26*2}{6}- \frac{55}{6} = [/latex] [latex]= \frac{52}{6}- \frac{55}{6} = [/latex] [latex]= \frac{52-55}{6} = \frac{-3}{6} =\frac{-1}{2} = -0.5[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы